Impelementasi dan Perwujuduan Hak Penyandang Disabilitas dalam Pemilihan Umum - Muh Yusril Sirman; Andi Tenri Famauri Rifai (Universitas Hasanuddin, 2023)
Suffrage is a form of political participation in a democratic country. The concept of political participation starts from the notion that sovereignty is in the hands of the people, which is carried out through joint activities to determine the goals and future of society and to determine the people who will hold the reins of leadership. So for citizens, the election becomes the channel of their will in determining the leader who will fight for their aspirations. This includes fulfilling and fighting for the rights of groups of persons with disabilities. The fulfillment and protection of political rights for persons with disabilities in Indonesia is still a problem, because there is still discrimination in the implementation of the fulfillment of political rights for persons with disabilities. So that an assessment is needed in order to find problems related to the voting rights of groups of persons with disabilities.